Kepemimpinan Perempuan dalam Al-Qur’an: Analisis Tafsir al-Qurṭubĭ dan Pemikiran Husein Muhammad - Nur Amaliah, Rizki; Munawaroh, Siti (REVELATIA Jurnal Ilmu al-Qur`an dan Tafsir, 2023)
This study aims to dig deeper regarding women's leadership in the Quran. The approach taken in this study is a qualitative method. Where the results are presented in the form of writing and sentences. Furthermore, this research uses the method of content analysis on the book of interpretation by al-Qurthubi known as Tafsir Al-Qurthubi. From the research results, it can be concluded that the Quran contains several verses related to women's leadership. Among them: Q.S An Nisa 34, Q.S An Naml 23-24, Q.S Ruum: 2. Which means the Qur'an does not prohibit women from being a leader. Women can lead as long as they meet the requirements as a leader and adhere to the rules of the Quran.